Promotive and Preventive Efforts of Health Workers in Reducing Stunting: A Scoping Review - Lilik Hanifah; Andari Wuri Astuti (Universitas Aisyah Pringsewu, 2023)
The role of health workers in increasing information related to stunting prevention and meeting the information needs of families is very important. Health promotion that is effective in preventing stunting can improve public health status. The purpose of this study is to find out the promotive and preventive efforts of health workers in reducing stunting. This study is a scoping review. Four databases were used to search the literature: PubMed, ScienceDirect, ProQuest, and Willey. The articles were selected using Prisma-Scr based on predetermined inclusion and exclusion criteria, and the critical appraisal was done using Mixed Method Appraisal Tool (MMAT). Ten articles that fit the objectives and criteria of the established literature study were found from 2,014 articles. The articles come from various countries: cross-sectional studies, quasi-experimental studies, case-control studies, and qualitative articles. Four themes were obtained, namely promotive and preventive efforts of health workers in pregnant women, promotive and preventive efforts of health workers in postpartum and breastfeeding mothers, promotive and preventive efforts of health workers in toddlerhood, and influencing factors. The conclusion is that promotive and preventive efforts of health workers in reducing stunting are needed, namely preventing anemia in pregnancy, nutritional counseling, exclusive breastfeeding, and feeding practices for toddlers. Abstrak: Peran tenaga kesehatan dalam meningkatkan informasi terkait pencegahan stunting dan memenuhi kebutuhan informasi keluarga sangat penting. Promosi kesehatan yang efektif dalam pencegahan stunting dapat meningkatkan derajat kesehatan masyarakat. Tujuan dari studi literatur ini untuk mengetahui upaya promotif dan preventif tenaga kesehatan dalam penurunan stunting. Metode yang digunakan dalam studi literatur ini adalah scoping review, pencarian literatur dalam studi ini menggunakan 4 database (PubMed, SciencDirect, ProQuest, Willey). Untuk seleksi artikel yang didapat berdasarkan kriteria inklusi dan eksklusi yang telah ditentukan, menggunakan Prisma-Scr untuk alur penyeleksian artikel, serta dilakukan critical apparaisal dengan menggunakan Mixed methods Appraisal Tool (MMAT). Hasil review dari total pencarian sebanyak 2.014 artikel, kemudian ditemukan 10 artikel yang masuk kedalam tujuan dan kriteria studi literatur yang ditetapkan. Artikel yang didapat berasal dari berbagai negara yang terdiri dari cross-sectional study, quasi-eksperimental study, case-control study dan kualitatif. Diperoleh 4 tema yaitu upaya promotif dan preventif tenaga kesehatan pada ibu hamil, upaya promotif dan prefentif tenaga kesehatan pada ibu postpartum dan menyusui, upaya promotif dan prefentif tenaga kesehatan pada masa balita dan faktor yang berpengaruh. Kesimpulan adalah dalam penurunan stunting diperlukan upaya promotif dan preventif dari tenaga kesehatan yaitu pencegahan anemia dalam kehamilan, konseling gizi, ASI eksklusif, dan praktik pemberian makan pada balita.